Insights Into the Molecular Evolution of AT-Hook Motif Nuclear Localization Genes in Brassica napus - Zhang, Wei-Meng; Fang, Da; Cheng, Xiu-Zhu; Cao, Jun; Tan, Xiao-Li (Frontiers in Plant Science, 2021)
AT-hook motif nuclear localization (AHL) proteins belong to a family of transcription factors, and play important roles in plant growth and development and response to various stresses through protein-DNA and protein-protein interactions. To better understand the Brassica napus AHL gene family, AHL genes in B. napus and related species were analyzed. Using Arabidopsis as a reference, 122 AHL gene family members were first identified in B. napus. According to the phylogenetic tree and gene organization, the BnaAHLs were classified into two clades (Clade-A and Clade-B) and three types (Type-I, Type-II, and Type-III). Gene organization and motif distribution analysis suggested that the AHL gene family is relatively conserved during evolution. These BnaAHLs are unevenly distributed on 38 chromosomes and expanded by whole-genome duplication (WGD) or segmental duplication. And large-scale loss events have also occurred in evolution. All types of BnaAHLs are subject to purification or neutral selection, while some positive selection sites are also identified in Type-II and Type-III groups. At the same time, the purification effect of Type-I members are stronger than that of the others. In addition, RNA-seq data and cis-acting element analysis also suggested that the BnaAHLs play important roles in B. napus growth and development, as well as in response to some abiotic and biotic stresses. Protein-protein interaction analysis identified some important BnaAHL-binding proteins, which also play key roles in plant growth and development. This study is helpful to fully understand the origin and evolution of the AHL gene in B. napus, and lays the foundation for their functional studies.